IgG dynamics of dietary antigens point to cerebrospinal fluid barrier or flow dysfunction in first-episode schizophrenia - Severance, Emily G.; Leweke, F. Markus (Brain, behavior and immunity, 2015)
Schizophrenia is a complex brain disorder that may be accompanied by idiopathic inflammation. Classic central nervous system (CNS) inflammatory disorders such as viral encephalitis or multiple sclerosis can be characterized by incongruent serum and cerebrospinal fluid (CSF) IgG due in part to localized intrathecal synthesis of antibodies. The dietary antigens, wheat gluten and bovine milk casein, can induce a humoral immune response in susceptible individuals with schizophrenia, but the correlation between the food-derived serological and intrathecal IgG response is not known. Here, we measured IgG to wheat gluten and bovine milk casein in matched serum and CSF samples from 105 individuals with first-episode schizophrenia (n=75 antipsychotic-naïve), and 61 controls. We found striking correlations in the levels of IgG response to dietary proteins between serum and CSF of schizophrenia patients, but not controls (schizophrenia, R2=0.34-0.55, p⩽0.0001; controls R2=0.05-0.06, p>0.33). A gauge of blood-CSF barrier permeability and CSF flow rate, the CSF-to-serum albumin ratio, was significantly elevated in cases compared to controls (p⩽0.001-0.003). Indicators of intrathecal IgG production, the CSF IgG index and the specific Antibody Index, were not significantly altered in schizophrenia compared to controls. Thus, the selective diffusion of bovine milk casein and wheat gluten antibodies between serum and CSF in schizophrenia may be the function of a low-level anatomical barrier dysfunction or altered CSF flow rate, which may be transient in nature.